Asphalt Concrete Mixtures: Requirements with regard to Life Cycle Assessment - Jan Mikolaj; Frantisek Schlosser; Lubos Remek; Aurelia Chytcakova (Advances in Materials Science and Engineering)
Design of asphalt concrete, required properties of constituent materials and their mixing ratios, is of tremendous significance and should be implemented with consideration given to the whole life cycle of those materials and the final construction. Conformity with requirements for long term performance of embedded materials is the general objective of the Life Cycle Assessment (LCA). Therefore, within the assessment, material properties need to be evaluated with consideration given to the whole service life—from the point of embedding in the construction until their disposal or recycling. The evaluation focuses on verification of conformity with criteria set for these materials and should guarantee serviceability and performance during their whole service life. Recycling and reuse of asphalt concrete should be preferred over disposal of the material. This paper presents methodology for LCA of asphalt concrete. It was created to ensure not only applicability of the materials in the initial stage, at the point of their embedding, but their suitability in terms of normatively prescribed service performance of the final construction. Methods described and results are presented in a case study for asphalt mixture AC 11; I design.